A randomized clinical trial of photodynamic therapy with methyl aminolaevulinate vs. diclofenac 3% plus hyaluronic acid gel for the treatment of multiple actinic keratoses of the face and scalp. (1st May 2014) - Zane, C.; Facchinetti, E.; Rossi, M.T.; Specchia, C.; Calzavara‐Pinton, P.G.
Summary: Background: A gel containing diclofenac and hyaluronic acid (DHA) and photodynamic therapy with methyl aminolaevulinate (MAL‐PDT) are widely used treatments for actinic keratoses (AKs). Objectives: The aim of this single‐centre, open‐label, prospective, nonsponsored, randomized controlled clinical trial was to compare the treatment results and cost‐effectiveness of MAL‐PDT and DHA. Methods: Patients with multiple AKs of the face and scalp were randomized to receive MAL‐PDT or DHA. After 90 days, the overall complete remission (CR) rate of patients and the CR rate of lesions according to thickness score were assessed, and patients and an investigator scored the cosmetic outcome. In addition, patients scored their overall satisfaction with the treatment. Patients with CR of all lesions were followed up for 12 months. Results: Two hundred patients with a total of 1674 AKs were enrolled. The lesion CR rates at 3 months were 85·9% with MAL‐PDT and 51·8% with DHA ( P < 0·0001). AKs of all thicknesses were significantly more responsive to MAL‐PDT. The patient CR rates at 3 months were 68% with MAL‐PDT and 27% with DHA. At the 12‐month examination, the number of patients with CR reduced to 37 with MAL‐PDT and seven with DHA. Rating of cosmetic outcome was very good or excellent in the vast majority of patients with both treatments. The analysis of cost‐effectiveness showed that the costs per patient with CR at 3 months and at 12 months are €566·7 and €1026·2, respectively, with MAL‐PDT and €595·2 and €2295·6, respectively, with DHA. Conclusions: Efficacy, cosmetic outcome and patients' overall satisfaction with MAL‐PDT are superior in comparison with DHA. MAL‐PDT is more expensive but it is more cost‐effective.